Effectiveness of the Edinburgh Postnatal Depression Scale (EPDS) as an early screening tool for detecting depression and anxiety in postpartum women - Khairiah, Rahayu; Yanti, Rizky; Hikmah, Nurul; Surahman, Heny (Media Penelitian dan Pengembangan Kesehatan, 2026)
Background: Depression and anxiety in postpartum women have a significant impact on the health of the mother, infant, and family. Early detection is essential to prevent long-term psychological complications. Objective: This study aimed to evaluate whether completing the Edinburgh Postnatal Depression Scale (EPDS), followed by a 20-minute brief education session delivered by midwives, could reduce EPDS scores among postpartum women within two weeks after the intervention. Methods: A quasi-experimental non-randomized controlled pre–post design was conducted at Pondok Bambu 1 Primary Health Center (intervention) and Pondok Gede District Hospital (control) using purposive sampling. A total of 52 postpartum women participated, with 26 assigned to the intervention group and 26 to the control group. The intervention consisted of EPDS screening followed by a brief education session on perinatal mental health, while the control group received routine care only. Results: Results showed that the mean EPDS score in the intervention group decreased from 13.23 ± 2.50 to 6.96 ± 2.18 (Δ = 6.27; 95% CI [−6.89; −5.65]; p < 0.001; d = 2.07), whereas the control group showed no significant change. The post-intervention Mann–Whitney test indicated a significant difference between groups (p = 0.021). Conclusion: These findings highlight that EPDS screening followed by brief education by healthcare providers is effective in reducing psychological distress in postpartum women. Integration of this program into postnatal care services is highly recommended to improve maternal and infant mental health outcomes.